The Application of Courtyard and Settlement Layouts of the Traditional Diyarbakır Houses to Contemporary Houses: A Case Study on the Analysis of Energy Performance - İdil Ayçam; Sevilay Akalp; Leyla Senem Görgülü (Energies, 2020)
Conventional energy use has brought environmental problems such as global warming and accelerated efforts to reduce energy consumption in many areas, particularly in the housing sector. For this purpose, bioclimatic design principles and vernacular architecture parameters have started to be examined in residential buildings nowadays. Thus, the demand for less energy-consuming houses has started to increase. In this study, we aimed to specify the significance of traditional architectural parameters for houses in the hot-dry climatic region of Diyarbakır, Turkey. Within the scope of the study, a case was based on the urban fabric of the traditional houses in Historical Diyarbakir Suriçi-Old Town settlement and the Şilbe Mass Housing Area was discussed. The courtyard types, settlement patterns, and street texture of traditional Diyarbakır houses were modeled by using DesignBuilder energy simulation program for the case study. Annual heating, cooling, and total energy loads were calculated, and their thermal performances were compared. The aim is to create a less energy-consuming and sustainable environment with the adaptation of traditional building form-street texture to today’s housing sector. Development of a settlement model, which is based on traditional houses’ bioclimatic design for hot-dry region, was intended to be applied in the modern housing sector of Turkey. Moreover, adapting local forms, urban texture, and settlement patterns to today has significant potential for sustainable architecture and energy-efficient buildings. According to this study, the optimum form and layout of traditional houses, which are one of the climate balanced building designs, provide annual energy savings if integrated and designed in today’s building construction. As a result of this study, if the passive design alternatives such as building shape, layout, and orientation were developed in the first stage of the design, energy efficient building design would be possible. The study is important for the continuation of traditional sustainable design.